ANALISIS EKSPOSUR NILAI TUKAR RUPIAH TERHADAP DOLLAR AMERIKA PADA INDUSTRI MANUFAKTUR YANG GO PUBLIC - Aryanti, Naning Wessiani; Basuki, Basuki (JURNAL BISNIS STRATEGI, 2005)
The primary objective of this research is to examine exchange rate exposure between Rupiah with American Dollar in manufacturing industrial sector that go public before and during crisis happened in Indonesia. Having found any significant exchange rate exposure in significant period, than this study will also evaluate which sub sectors in manufacturing industrial sector are exposed with the fluctuation of exchange rate.The data was collected using pooling method. Thirty-eight firms were chosen and divided into seven sub sectors. The statistical method used to test hypothesis is multiple regressions.The empirical results show that significant exchange rate exposure is only found in manufacture industry during crisis period, and from seven subsectors only three sub sectors (food and beverage, pharmaceuticals, and plastics) that significantly exposed because of the exchange rate fluctuation. This result shows that all firms must considered exchange rate management to reduce the exposure.